(untitled) (Research, Society and Development, 2021)
Vaccines are substances used in the prevention and control of diseases, and even though they are effective and safe, they can cause adverse events that can be multifactorial. In this context, the means of regulation in the country have improved over the years, and bodies such as the National Health Surveillance Agency (ANVISA) have emerged, which, through resolutions and regulations, carry out the regulation and registration of vaccines. This article is a narrative bibliographic review where articles with publications between 2014 and 2020 were used, in addition to official documents with historical and legal value, in order to demonstrate the role of ANVISA in the process of vaccine regulation. Through resolutions and norms, the aforementioned agency carries out the regulation and registration of vaccines, playing an extremely important role in the inspection of the clinical studies process, verifying compliance with all current regulations, acting in the inspection of good manufacturing practices, in order to regularize the commercialization of vaccines, still having a fundamental role in the applicability of these vaccines in view of the regulation of minimum standards for vaccination sites. With this, the present study provides a broad view about the role of ANVISA in the process of regulation of vaccines, thus contributing to the knowledge of its regulations that view the safety of population health.